Reversing the biblical tide: what Kuruman teaches London about mission in a post-colonial era - S. de Gruchy (Acta Theologica)
Through a case study focusing on the shift from the London Missionary Society (LMS) to the Council for World Mission (CWM) this essay argues that there is a hermeneutical circle between the Bible and mission. A particular reading of the Bible led the missionaries of the LMS to Africa, and their concern to promote the Bible led to the translation and printing of the Bible in indigenous languages — most famously into Setswana by Robert Moffat at Kuruman. Inevitably, the availability of the Bible in indigenous languages led to new ways of understanding the church and mission from the perspective of the South. This post-colonial dynamic led to changes in the LMS and to the emergence of CWM in 1977. The essay then pursues the argument by showing how over the thirty years of CWM’s life there continues to be the development of a biblical vision for mission that takes seriously the perspectives of the post-colonial world.